2015
DOI: 10.1016/j.jajs.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of chondrogenesis from cartilage tissue and alginate encapsulated human adipose stem cells

Abstract: Available online xxxKeywords: Articular cartilage Sodium alginate Chondrogenesis Extra-cellular matrix (ECM) Differentiation a b s t r a c t Aim: Alternate strategies to regenerate the damaged tissue require exogenous supply of several chondrocyte implants. There are inherent challenges to optimize an appropriate tissue culture methodology that can aid in enrichment of chondrocytes. The aim of the study was to explore the differentiation potential, expansion and growth kinetics of the human adipose derived ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Many other biomaterials have been employed for culturing ASCs in 3D environments, such as chitosan [ 75 ], silk [ 76 ], alginate [ 77 , 78 ], and natural and synthetic calcium phosphate [ 7 ]. Various scaffolds with different tissue properties including geometry, porosity, stiffness, surface characteristics, and composition have been tested.…”
Section: Asc's Growth and Differentiation On Biofabricated 3d Scafmentioning
confidence: 99%
See 2 more Smart Citations
“…Many other biomaterials have been employed for culturing ASCs in 3D environments, such as chitosan [ 75 ], silk [ 76 ], alginate [ 77 , 78 ], and natural and synthetic calcium phosphate [ 7 ]. Various scaffolds with different tissue properties including geometry, porosity, stiffness, surface characteristics, and composition have been tested.…”
Section: Asc's Growth and Differentiation On Biofabricated 3d Scafmentioning
confidence: 99%
“…Alginate is a natural hydrogel and has been widely used for tissue engineering applications. It has been also reported that ASCs could be differentiated to other cell types in alginate scaffolds [ 77 , 78 , 85 ]. During printing, a laser pulse was applied to the energy absorbing layer (red layer), generating a high-pressure bubble and propelled the suspended cells below that area.…”
Section: Asc's Growth and Differentiation On Biofabricated 3d Scafmentioning
confidence: 99%
See 1 more Smart Citation